(untitled) (Medico Legal Update, 2021)
Preeclampsia in Indonesia remains a huge problem during pregnancy with high morbidity and mortality. Many risk factors influence the occurrence of preeclampsia, such as the family history of preeclampsia, kidney disease, diabetes mellitus, chronic hypertension that has been suffered previously by pregnant mothers before pregnancy (preeclampsia superimposed), obesity, and postpartum depression. The research objective was to determine the relationship between preeclampsia and the occurrence of postpartum depression in Masyita Delivery Hospital Makassar. This study used quantitative research method with a cross-sectional design. Sampling using purposive sampling with a sample size of 61 postpartum mothers. Collecting data using a questionnaire and analyzed using the Chi-Square test. This study found that pregnant mothers who experienced mild preeclampsia were 34 subjects with 8.8% of them had postpartum depression, severe preeclampsia experienced by 7 subjects with 71,4% of them had postpartum depression. The results of statistical tests using Chi-square obtained the p-value=0.001. This study concluded that there is a significant relationship between preeclampsia and the incidence of postpartum depression in Masyita Delivery Hospital Makassar, Indonesia.